Un nuovo sguardo dalla (e sulla) letteratura tedesca contemporanea: l'Adelbert-von-Chamisso-Preis (Altre Modernità, 2015)
The Adelbert-von-Chamisso-Preis is a literary prize awarded by the Robert Bosch Stiftung to non-German authors who write in German and chose this language as their form of expression. Since the first prizes were awarded in 1985, 65 writers from more that twenty different countries have won the award. It was Harald Weinrich who convinced the Bosch Stiftung of the value of establishing the Adelbert-von-Chamisso-Preis. In the 1980s, the prize was awarded to what was still called ‘Gastarbeiterliteratur’ and the stress was laid on the writers’ condition of foreigners in Germany rather than on the quality of their literary work, whereas today it has become a substantial part of contemporary German literature and it is sometimes called ‘Chamisso-Literatur’. However, it may be argued that the use of this term, even though it isn't as unsatisfactory as ‘Gastarbeiterliteratur’ or ‘Migrantenliteratur’, still implies that this kind of literature isn't ‘genuine’ German literature. Maybe non-German authors don't need their work to be defined by a special term and some of them don't want a special literary prize either. The question about the ‘Chamisso-Literatur’ is still under discussion. Nevertheless the Adelbert-von-Chamisso-Preis has undoubtedly contributed to spread German literature by non-German authors and to improve its reception.
Keywords: Chamisso-Preis; Chamisso-Literatur; Bosch Stiftung; Harald Weinrich; letteratura transculturale tedesca